Extended-Spectrum Beta-Lactamase-Producing Enterobacteriaceae in Effluents of Different Hospitals Sewage in Biratnagar, Nepal - Mahato, Sanjay; Mahato, Ajay; Adhikari, Prajjwal (International Journal of Environment, 2019)
Untreated water from hospitals of Biratnagar as effluent is a serious concern from health point of view. Antimicrobial resistant bacteria are a serious threat which may contaminate the drinking water and environment. With an aim of isolation and detection of Multidrug resistance (MDR) and Extended-spectrum b- lactamases (ESBL) producing Enterobacteriaceae from the effluents and sewage samples of hospitals, this study builds the importance to inquiry about the involvement of hospital liquid waste discharge in the development and distribution of antibiotics resistance in the environment bacteria. Ten hospital sewage samples were aseptically collected, processed and analyzed. Isolates were biochemically identified, and their antimicrobial activity were tested. Of the ten sewage samples analyzed, 23 bacteria isolates were isolated which contained 8 Escherichia coli (34.7%), 5 isolates each of Citrobacter spp (21.7%) and Enterobacter spp (21.7%), 3 isolates of Klebsiella spp (13%), and 1 isolate each of Shigella spp (4.3%) and Yersinia spp (4.3%). Most of the bacteria isolated were resistant to ampicillin, ceftazidime, cefpodoxime, amoxicillin/clavulanate, cefotaxime, cefoxitin, ceftriaxone, and cefuroxime. The isolates were sensitive to nitrofurantoin, azithromycin, trimethoprim/sulfamethoxazole, chloramphenicol, ciprofloxacin, ofloxacin, and gentamycin antibiotics. Out of twenty-three isolates, 16 (69.6%) were found to be multidrug resistant, 7 (30.4%) were producing extended beta lactamase, while 18 (78.3%) multi-antibiotics resistance index greater than 20%. Among the bacteria isolated; 80% of the Citrobacter; and 75% of the E. coli were found biofilm producing bacteria. Sewage treatment plant must be established in hospital for their effluents and sludge coming from the hospital.